Good Governance Based on Islamic Values ​​in PTKIN Personnel Management: A Case Study - Andriani, Idaya; Hamengkubuwono; Azwar, Beni; Syafei, Indrayanto (LETIGES, 2026)
This research is motivated by the increasing demands for accountability, transparency, and effectiveness of higher education governance, particularly at State Islamic Religious Higher Education Institutions (PTKIN), which are faced with the need to integrate sound governance principles with Islamic values. Despite the widespread implementation of good governance, institutions still struggle to operationalise Islamic values concretely in personnel management practices. Therefore, this study aims to analyse the implementation of Islamic-based sound governance principles, identify supporting and inhibiting factors, assess their impact on employee performance, and formulate optimisation strategies at the State Islamic Institute (IAIN) Curup as a non-metropolitan PTKIN. This study uses a qualitative approach with a case study design, through in-depth interviews, participant observation, and document analysis, which are analysed using reflective thematic analysis. The results show that the institution has integrated the implementation of sound governance with Islamic values such as amanah, syura, ihsan, and ‘adl, thereby forming a holistic governance model based on spiritual values. This integration has a positive impact on motivation, loyalty, professionalism, and organisational performance, although it still faces structural and cultural obstacles and limited digital capacity. Optimisation strategies include strengthening Islamic leadership, developing human resource capacity, values-based digitalisation, and strengthening organisational culture. This research is limited by its single-case focus and qualitative approach, resulting in limited generalizability. The implications of this research enrich the development of good governance and Islamic work ethics theory with a hybrid governance model based on Islamic values, and provide practical recommendations for PTKIN management. The novelty of this research lies in the operationalisation of Islamic values ​​in personnel governance practices in an integrative and contextual manner.